A solar tube: Efficiently converting sunlight into electricity and heat. (January 2019) - Xiang, Chengjie; Zhao, Xiaoli; Tan, Liwang; Ye, Jiaye; Wu, Sujuan; Zhang, Sam; Sun, Lidong
Abstract: A solar cell, capable of directly converting solar energy into electricity, bears a Shockley-Queisser limit of about 31% based on a single pn junction. In general, less than 50% of the solar irradiation spectrum (mostly in the ultraviolet and visible regions) can be utilized for the conversion. As such, the theoretical utilization rate is less than 15% in a single device, with most of the extra energy being lost as heat. It is thus appealing to enhance the energy utilization with devices that could collect the heat loss. In this study, we design and demonstrate a solar tube to realize photo-electric and photo-thermal conversions simultaneously. The key point is the use of titanium tube: (1) it has a small plasma frequency to enable wide absorption for thermal conversion; (2) it accommodates TiO2 nanotube arrays to solve the cracking problem under tensile stress. A sandwiched membrane of high transparency and conductivity is developed for hole transport and collection. Eventually, a total energy efficiency of about 25.2% is obtained. Such a solar tube is anticipated to highly boost the utilization rate of solar energy with judiciously designed structure. Graphical abstract: A solar tube integrating the photo-electric and photo-thermal conversion is developed in this study, with a total efficiency of about 25.2%. The key component is the titanium tube used, which has a small plasma frequency to enhance the light harvesting and accommodates the nanotube arrays to release the tensile stress. fx1 Highlights: A solar tube integrating the photo-electric and photo-thermal conversion is demonstrated. The titanium having small plasma frequency is selected to enable wide absorption of photon energy for thermal conversion. A sandwiched membrane of high transparency and conductivity is developed for tubular solar cells.